Development and Initial Validation of the Confidence and Motivation to Teach Primary Physical Education Questionnaire - Spittle, Sharna; Watt, Anthony P.; Spittle, Michael (Frontiers in Education, 2022)
This research describes the development and psychometric evaluation of the Confidence and Motivation to Teach Primary Physical Education Questionnaire (CMTPPEQ). Phase 1 involved questionnaire development and quantitative analysis of reliability and use of exploratory factor analysis (EFA) to examine factor structure and validity with 161 pre-service teachers. The EFA revealed two confidence factors and five motivation factors. All factors displayed adequate internal consistency and acceptable test-retest reliability for the confidence factors and three motivation factors. In Phase 2, the measure was further evaluated and factor structure refined using confirmatory factor analysis (CFA), with 211 pre-service and 107 in-service teachers. The two-factor confidence structure of Management and Planning and Implementation was confirmed with acceptable levels of fit. Structural changes made to the motivation structure resulted in six factors: Intrinsic – Affective (Practice), Intrinsic – Affective (Knowledge), Extrinsic – Student Outcomes, Introjected Performance, Extrinsic – Professional Expectations, and Amotivation. All factors demonstrated adequate internal consistency.